Amitriptyline revitalizes ICB response via dually inhibiting Kyn/Indole and 5-HT pathways of tryptophan metabolism in ovarian cancer - Junyang Li; Bingjie Mei; Lu Feng; Xiaoxin Wang; Dengfeng Wang; Jianming Huang; Guonan Zhang (iScience)
Summary: Reprogramming tryptophan metabolism (TRP) may be able to overcome immunosuppression and restore the immune checkpoint blockade (ICB) response in patients with epithelial ovarian cancer (EOC) resistant to ICB therapy because TRP metabolism is involved in the kynurenine/indole and serotonin pathways of tryptophan metabolism. Herein, employing amitriptyline (AMI), an antagonist of TLR4 and serotonin transporter (SERT), we revealed that AMI remodels the immunological landscape of EOC. In particular, AMI lowered the expression of IDO1, IL-4I1, and PD-L1, the quantity of KYN and indoles, and the level of immunosuppressive immune cells MDSC, Tregs, and CD8+CD39+/PD-1+ T cell. AMI boosted the killing potential of anti-PD-1-directed CD8+T cells and worked in concert with PD-1 inhibitors to suppress tumor growth and to prolong the survival of EOC-bearing mice. This work highlights AMI as an effective regulator of ICB response by manipulating EOC cell TRP metabolism, indicating it could be a potential strategy for improving EOC ICB therapy.